2020
DOI: 10.1016/j.jcyt.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic dendritic cell vaccination controls pancreatic cancer growth in a mouse model

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is the 4 th leading cause of cancer-related deaths with high recurrence after surgery due to a paucity of effective post-surgical adjuvant treatments. DC-vaccines can activate multiple anti-tumor immune responses but have not been explored for PDAC treatment. No standard delivery route has also been established for DC vaccination, but intraperitoneal (IP) delivery is of particular interest because it allows increased DC-vaccine dosage and thus migration to draining lymph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…It was observed that prophylactic DC vaccination inhibited tumor growth in mice. The same was observed in a prophylactic vaccination study in a pancreatic cancer model (pancreatic ductal adenocarcinoma) (Shangguan et al, 2020). These data suggest that vaccination alone used autonomously can be an efficient adjunct tool in the clinical setting.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It was observed that prophylactic DC vaccination inhibited tumor growth in mice. The same was observed in a prophylactic vaccination study in a pancreatic cancer model (pancreatic ductal adenocarcinoma) (Shangguan et al, 2020). These data suggest that vaccination alone used autonomously can be an efficient adjunct tool in the clinical setting.…”
Section: Discussionsupporting
confidence: 74%
“…Vaccination strategies have been developed considering these particular coordination properties of immune responses (Bauer et al, 2011;Markov et al, 2015;Shangguan et al, 2020;Simon et al, 2009). Therefore, the identification of protocols that result in a potent, robust, and lasting immune response that promote regression or eradication of tumors, has been the focus of several studies (Lopes et al, 2017;Palucka & Banchereau, 2013;Perez & De Palma, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies demonstrated ADC function in IRE tumor ablation and DC vaccination, respectively. 13,[32][33][34] Another limitation was that MRI approaches utilized in this study do not directly describe the effects on tumor cell membrane integrity. Functional MRI techniques to detect tumor cell membrane permeability are needed in this area to further study the effect of combination therapy on tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a phase I study, the effect of allogeneic tumor lysate–loaded autologous monocyte-derived DCs was evaluated in the treatment of resected PDAC and the vaccination treatment indicated a feasible and safe immune reactivity induction capability ( 48 ).The prophylactic DC vaccination strategy used DC vaccines generated by ex vivo differentiation, and the maturation of bone marrow–derived precursors was investigated in PDAC tumor mice models and exhibited a significant effect in inhibiting recurrent tumor growth and extending the survival time ( 49 ). It was well known that in PCs, the telomerase [human telomerase reverse transcriptase (hTERT)] is a promising target antigen and it mainly expresses in cancer stem cells that are difficult to eliminate by common therapeutic strategies ( 50 ).…”
Section: Dendritic Cell Vaccines Of Pancreatic Cancermentioning
confidence: 99%